Modern Magnetic Resonance - Webb, Graham A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This completely revised and updated second edition showcases the considerable progress that has taken place in this field since 2008. The three part reference work contains key developments, scores of contributions, key literature citations and overviews of the important progress achieved in the relevant topics since the publication of the previous edition. Two key differences in this new edition are the replacement of the previous Medical Sciences section with the Biological and Pharmaceutical Science sections and the inclusion of a new part featuring Archaeological applications. Divided into seven comprehensive parts, the work covers: Archaeology, Biological Sciences, Chemistry, Food Science, Marine Science, Materials Science, and Pharmaceutical Science. Section editors from Asia, USA, and Europe have recruited a truly international list of active and eminent contributors who have created a remarkable and unique work.  Topics include: Electron Spin Resonance, High resolution solid and liquid state NMR; Low resolution NMR; Solution State NMR; Magnetic Resonance Imaging. The level of scientific coverage of the chosen topics renders the handbook suitable for research workers in the relevant fields as well as final year undergraduate students. .
Spectroscopy in Breast Cancer -- In Vivo Molecular MR Imaging: Potential and Limits -- In vivo 13C MRS -- Magnetic Resonance Spectroscopy and Spectroscopic Imaging of the Prostate, Breast, and Liver -- MR-Mammography -- Phosphorus Magnetic Resonance Spectroscopy on Biopsy and In Vivo -- Radio Frequency Coils for Magnetic Resonance Spectroscopy -- Spatially Resolved Two-Dimensional MR Spectroscopy in vivo -- Overview of NMR in the Pharmaceutical Sciences -- Instrumentation -- Applications of Cryogenic NMR Probe Technology for the Identification of Low-Level Impurities in Pharmaceuticals -- Flow NMR Techniques in the Pharmaceutical Sciences -- Developments in NMR Hyphenation for Pharmaceutical Industry -- LC-NMR in Dereplication and Structure Elucidation of Herbal Drugs -- Techniques -- New Approaches to NMR Data Acquisition, Assignment and Protein Structure Determination: Potential Impact in Drug Discovery -- Transferred Cross-Correlated Relaxation: Application to Drug/Target Complexes -- Novel Uses of Paramagnets to Solve Complex Protein Structures -- Fast Assignments of 15N-HSQC Spectra of Proteins by Paramagnetic Labeling -- Phospholipid Bicelle Membrane Systems for Studying Drug Molecules -- Partial Alignment for Structure Determination of Organic Molecules -- Measurement of Residual Dipolar Couplings and Applications in Protein NMR -- Using Chemical Shift Perturbations to Validate and Refine the Docking of Novel IgE Antagonists to the High-Affinity IgE Receptor -- Du.
Keywords: Materials -- Analysis; Pharmaceutical chemistry; Archaeology; Medicine -- Research; Biology -- Research; Food science; Water; Hydrology; Characterization and Analytical Technique; Pharmaceutics; Archaeology; Biomedical Research; Food Science; Water